wintertwothousand
New member
- Joined
- Feb 11, 2009
- Messages
- 2
Here is the problem:
(1/2)t^2 - 5t + 25 = -t^2 + 6t + 16
I know I must subtract the right side, thereby setting it to 0, but when I do this I get 1.5t^2 - 11t + 9 = 0. How is it possible to plug this into a quadratic formula when I have a negative for my square root?
The answer key says t= 0.94 how did they find this??
(1/2)t^2 - 5t + 25 = -t^2 + 6t + 16
I know I must subtract the right side, thereby setting it to 0, but when I do this I get 1.5t^2 - 11t + 9 = 0. How is it possible to plug this into a quadratic formula when I have a negative for my square root?
The answer key says t= 0.94 how did they find this??